Trouble makers - Taylor, A. J. P. (London, 1957)
The historian, particularly the historian of foreign policy, finds it hard to escape the Tribal Gods. We may remind our selves over and over again that the foreign policy of a country is made by a few experts and a few rather less expert politi cians. We may try to bring out the cross-currents which push foreign policy first in one direction, then in another. We may resist the assumption that governments are always in line with public opinion, and still more the assumption that public opinion, even if it can be ascertained, is ever in fact the opi nion held by everyone in the country. But the Tribal Gods are always breaking in. We have to treat foreign policy as a block, a solid lump, if we are going to get through the story at all. We write 'the British' when we mean 'the few mem bers of the Foreign Office who happened to concern them selves with this question'. Great Britain is made to move with the ponderous certainty of John Bull. In the end we build up a picture of an apostolic succession, in which statesmen moving from one muddle to the next display.
Keywords: International relations